PENGETAHUAN HAID PADA REMAJA DI MANADO - Kujangke, Freddy; Lengkong, Rudy A.; Suparman, Eddy (Universitas Sam Ratulangi, 2013)
Abstract: Backgrounds Dysmenorrhea is the most common gynecological symptom reported in adolescents. Prevalence estimates vary from 45% to 75%. Absenteeism from work and school as a result of dysmenorrhoea is common (13% to 51% women have been absent at least once and 5% to 14% are often absent owing to the severity of symptoms). Dysmenorrhea association with psychologist and behavior factors and its effects their physical activities and school performance. Some studies had shown that association between school performance with dysmenorrhea.Objective To assess the comparison between school performance with and without dysmenorrhea in pubertal adolescents. Methods A cross sectional study was conducted on Juni 2010.The samples were recruited with simple randomization in adolescents aged 10 until 18 years old at school of Musthafawiyah Mandailing Natal districs. All subjects who met the inclusion criteria were assessed their school performance on 2 consecutive semester in one year. In order to assessed the comparison between school performance with or without dysmenorrhea used X2 test. Results One hunderd and sixteen subject were participated in this study. After measured the school performance. No significant different on school performance with and without dysmenorrhea in two group (P=0.176 and P=008, 95%CI -0.05 to 0.05). Conclusion: There was no significant difference school performance between with and without dysmenorrheal. Keywords: Dysmenorrhea, school performance, pubertal adolescent. Â Â Abstrak: Latar belakang Nyeri haid merupakan nyeri yang terjadi selama masa menstruasi.Angka kejadian nyeri haid berkisar antara 45% sampai 75% dari seluruh remaja perempuan pubertas. Dimana ketidak hadiran di sekolah berkisar antara 13% sampai 51% serta 5% sampai 14% ketidak hadiran tersebut disebabkan beratnya gejala yang terjadi. Nyeri haid berhubungan dengan faktor perilaku dan psikologis. Selain itu dapat menyebabkan pembatasan aktifitas sekolah dan prestasi akademik. Beberapa studi telah menunjukkan adanya kaitan prestasi akademik dengan nyeri haid. Tujuan Untuk mengetahui perbandingan prestasi akademik dengan dan tanpa nyeri haid pada anak perempuan pubertas. Metode Studi ini merupakan studi cross sectional. Pemilihan sampel secara acak sederhana yang dilakukan pada anak remaja perempuan yang berusia 10 sampai 18 tahun di SMP St Theresia Malalayang dan SMA St Theresia Malalayang Manado yang dilakukan pada bulan Desember 2011. Semua subjek yang memenuhi kriteria inklusi dinilai prestasi akademik selama dua semester berturut-turut.Untuk menilai perbandingan prestasi akademik dengan atau tanpa nyeri haid digunakan uji X2. Hasil Seratus enam belas subjek berpartisipasi dalam penelitian ini. Setelah dinilai prestasi akademik. Ditemukan bahwa tidak terdapat perbedaan yang bermakna antara prestasi akademik dengan atau tanpa nyeri haid (P 0.176 vs P: 0.08). IK 95%:-0.05; 0.05. Simpulan: Tidak ditemukan adanya hubungan prestasi akademik dengan dan tanpa nyeri haid. Kata kunci: Nyeri haid, prestasi akademik, perempuan pubertas